IS THE SIZE OF PUBLIC SECTOR DETERMINING IN ACHIEVING MACROECONOMİC STABILITY? THE CASE OF TURKEY - Köstekçi, Ahmet; Ceyhan, Turgay; Gürsoy, Samet (Fırat University, 2021)
It is argued that the economy model, in which the public sector is predominant, provides more advantages than the economy model in which the market economy is effective in the process of ensuring macroeconomic stability, and this is a requirement of the welfare state understanding. From this basic view, the relationship between the economic size of the public sector and macroeconomic stability was examined in the study, in which Turkey?s data for the period 1980-2019 was used. According to the causality test results of Toda and Yamamoto (1995), it was concluded that there is a causal relationship from public expenditures to economic growth and inflation, but there is no causality relationship to unemployment. These results provide important evidence that changes in the size of the public sector are the cause of changes in economic growth and inflation.

Kamu sektörünün ağırlıklı olmuş olduğu ekonomi modelinin, makroekonomik istikrarın sağlanması sürecinde piyasa ekonomisinin etkin olduğu ekonomi modeline göre daha fazla avantaj sağladığı ve bunun refah devleti anlayışının bir gereği olduğu savunulmaktadır. Bu temel görüşten hareketle Türkiye’nin 1980-2019 dönemine ait verilerin kullanıldığı çalışmada, kamu sektörü ağırlığı ile makroekonomik istikrar arasındaki ilişki incelenmiştir. Yapılan Toda ve Yamamoto (1995) nedensellik testi sonuçlarına göre kamu harcamalarından ekonomik büyüme ve enflasyona doğru nedensellik ilişkilerinin olduğu, ancak işsizliğe doğru bir nedensellik ilişkisinin olmadığı sonucuna ulaşılmıştır. Bu sonuçlar, kamu sektörü ağırlığındaki değişimlerin, ekonomik büyüme ve enflasyondaki değişimlerin nedeni olduğu noktasında önemli kanıtlar sunmaktadır.
Makroekonomik İstikrarın Sağlanmasında Kamu Sektörünün Büyüklüğü Belirleyici mi? Türkiye Örneği